Pengaruh Manfaat Keyakinan dan Dimensi Kepribadian Terhadap Loyalitas Pelanggan Melalui Relationship Quality (Studi pada Pelanggan Busana Muslimah di Kota Malang) - Mufidha Kartika Yudha; Margono Setiawan; Christin Susilowati (Akutansi Bisnis & Manajemen ( ABM ), 2014)
Aims of this study to analyze the influence of confidence benefit and personality dimensions on customer loyalty through relationship quality with 84 customers of Muslim clothing boutique in Malang in 2014 as a sample and using quantitative explanatory as the research approach. The sampling technique used is purposive sampling. The analysis techniques were using descriptive statistics and path analysis. The results of the study showed that the confidence benefits and personality dimensions influence loyalty through relationship quality. However, the confidence benefit does not directly influence loyalty. This study shows that the confidence benefits proved to have no effect on loyalty if only seen from Muslim clothing prices, but other factors that support. So, the role of the employee as an intermediary fashion boutique owner as providers and customers as users is very important. In this case, the communication skills of employees are very important to build trust, and commitment to customer satisfaction which leads to customer loyalty.